Analysis and control of enhanced switched boost inverters for wide duty cycle operation - Kumar A.; Raghuram M.; Singh S.K.; Xiong X.; Reza M. (My University, 2025)
Switched boost inverter (SBI) is a high gain converter that uses the concept of Z-source inverter but with a reduced number of passive elements. The analysis and operation of SBI are already reported for continuous and discontinuous input current but these converters operate in the restricted range of duty cycle and load variation. In a certain duty cycle situation, the converter shows inadvertent behavior and the inductor current tends to become equal to the AC load current. This phenomenon creates a ripple in dc link voltage which causes increased THD at the output AC voltage. Moreover, the DC link capacitor undergoes higher voltage stress. In this paper, the duration for which this peculiar phenomenon lasts is termed as non-zero discontinuous current mode (NZ-DCM) of operation. The analytical expression during NZ-DCM is derived and analyzed in terms of peak to peak ripple inductor current. To overcome NZ-DCM, the authors propose a modified SBI which consists of an extra active switch antiparallel across the diode. The simulation and experimental results pertaining to the adverse effect of NZ-DCM and its mitigation in the form of the conventional and modified SBI are presented in this paper. © 2013 IEEE.